IoT-Based Integrated Monitoring System for Household Water Level and Usage Tracking - Rivaldi, Muhammad Rizki; Said, Fadillah (Journal Innovations Computer Science, 2025)
Conventional household water management often results in inefficiencies, including tank overflow, unexpected shortages, and a lack of awareness about daily consumption. Most existing solutions address these issues only partially—either by monitoring water levels, automating pump control, or recording usage data—without integrating the three into a unified system. To address this gap, this research developed and validated a low-cost Internet of Things (IoT) prototype that combines real-time water-level monitoring, daily consumption measurement, and automatic pump control within a smartphone-connected platform. The system is built on a NodeMCU ESP8266 microcontroller equipped with an HC-SR04 ultrasonic sensor, a YF-S201 flow sensor, and a relay-controlled pump, with data transmitted via Wi-Fi to the Blynk application. Using a Research and Development (R&D) methodology with a prototyping model, the study conducted functional, accuracy, and usability testing. Results show that the prototype achieved reliable performance, with an average error below 2% for both sensors and stable operation during 24-hour trials. Beyond technical validation, the system demonstrated its potential as an eco-feedback tool by providing clear consumption data that can encourage more sustainable water use at the household level.